Analisis Faktor yang Berpengaruh Terhadap Pendapatan UMKM Sektor Industri Makanan Ringan di Kecamatan Padang Utara: Analisis Faktor yang Berpengaruh Terhadap Pendapatan UMKM Sektor Industri Makanan Ringan di Kecamatan Padang Utara - Syamra, Yesmira (Perkumpulan Doktor Indonesia Maju, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role in increasing national economic growth. So it is very important to do research to analyze the factors that can affect the income of MSMEs. This study aims to analyze the effect of the level of education, capital and labor on the income of SMEs in the snack industry sector in the North Padang District and can provide policy-related analysis in improving the development of MSMEs. In this study, there were 39 MSME palaku units engaged in the snack industry sector in the North Padang District, Padang City, West Sumatra Province, which became the research sample of 210 populations of MSMEs registered in the North Padang district. Samples were taken using purposive sampling method. The analysis method used for testing the truth of the hypothesis is regression analysis processed with SPPS 16.0. The results of hypothesis testing that have been carried out show that the education level of MSME actors has a significant effect on the income of the SME sector in the snack industry sector in North Padang District. Likewise, capital and labor have a significant influence on the income of SMEs in the snack industry sector in North Padang District.